THE IMPACT OF USING MODERN INFORMATION TECHNOLOGY METHODS ON RATIONALIZING THE COSTS OF HEALTH CARE SERVICES - AN EXPERIMENTAL STUDY (World Economics and Finance Bulletin, 2025)
This research aims to examine the role of information technology in enhancing the quality of healthcare services by analyzing the characteristics and advantages of IT, in addition to reviewing the distinctive features of healthcare services and the objectives of service quality provided. The research concludes that information technology represents a fundamental pillar for improving operational efficiency, reducing costs, and enhancing accurate decision-making in healthcare institutions. It also reveals that the unique characteristics of healthcare services, such as intangibility, interdependence, and heterogeneity, pose challenges that require the use of advanced technological solutions to support performance and improve patient satisfaction. The research also emphasizes that achieving quality healthcare services includes enhancing care efficiency, patient safety, reducing costs, developing professional performance, and promoting equity and health prevention. In light of this, the integration of information technology into the healthcare sector becomes a strategic necessity to achieve effective and sustainable healthcare that benefits both individuals and society
Keywords: Information technology; service costs; health sector